Sequential induction of auxin efflux and influx carriers regulates lateral root emergence - Benjamin Péret; Alistair M Middleton; Andrew P French; Antoine Larrieu; Anthony Bishopp; Maria Njo; Darren M Wells; Silvana Porco; Nathan Mellor; Leah R Band; Ilda Casimiro; Jürgen Kleine‐Vehn; et al. (Molecular Systems Biology, 2013)
Abstract In Arabidopsis, lateral roots originate from pericycle cells deep within the primary root. New lateral root primordia (LRP) have to emerge through several overlaying tissues. Here, we report that auxin produced in new LRP is transported towards the outer tissues where it triggers cell separation by inducing both the auxin influx carrier LAX3 and cell‐wall enzymes. LAX3 is expressed in just two cell files overlaying new LRP. To understand how this striking pattern of LAX3 expression is regulated, we developed a mathematical model that captures the network regulating its expression and auxin transport within realistic three‐dimensional cell and tissue geometries. Our model revealed that, for the LAX3 spatial expression to be robust to natural variations in root tissue geometry, an efflux carrier is required—later identified to be PIN3. To prevent LAX3 from being transiently expressed in multiple cell files, PIN3 and LAX3 must be induced consecutively, which we later demonstrated to be the case. Our study exemplifies how mathematical models can be used to direct experiments to elucidate complex developmental processes.